Impaired sexual activity in young ischaemic stroke patients: an observational study. (7th October 2013) - Bugnicourt, J.‐M.; Hamy, O.; Canaple, S.; Lamy, C.; Legrand, C.
<x xml:space="preserve">Abstract</x> Background and purpose The present study sought to determine the impact of stroke on sexual function and well‐being in a cohort of young ischaemic stroke patients and identify factors associated with impairment. Methods Over a 2‐year period, all patients aged 60 or under with ischaemic stroke or transient ischaemic attack (n = 156) were included. Information on sexual function and well‐being was obtained by means of a paper questionnaire mailed to participants 1 year after their stroke. Impaired sexual activity (ISA) was defined as a decline in sexual function and/or satisfaction. Psychological well‐being was evaluated on the Hospital Anxiety and Depression Scale (HADS). Results The response rate was 67% (n = 104). Thirty of these responders (29%) reported ISA. Patients with ISA had a higher HADS score (19.7 vs. 11.2 in patients with no impairment; P < 0.001), anxiety score (10.0 vs. 6.3; P < 0.001) and depression score (8.7 vs. 4.8; P < 0.001) and were more likely to have left brain lesions (70% vs. 30%; P < 0.001) and use angiotensin‐converting enzyme (ACE) inhibitors (73% vs. 31%; P < 0.001) and diuretics (50% vs. 19%; P = 0.003). In a stepwise logistic regression, depression (odds ratio 9.1, 95% confidence interval 2.45−33.46; P = 0.001) and ACE inhibitor use (odds ratio 6.0, 95% confidence interval 2.11−17.28; P = 0.001) were associated with ISA. Conclusions Impaired sexual activity was reported by almost one‐third of younger patients 1 year after ischaemic stroke. Factors associated with post‐stroke ISA may include specific medications and depression rather than the characteristics of the stroke per se.